Synthesis and Characterization of Calcium Oxide Impregnated on Silica from Duck Egg Shells and Rice Husks as Heterogeneous Catalysts for Biodiesel Synthesis - Haryono Haryono; Safri Ishmayana; Isy Fauziyah (مجلة بغداد للعلوم)
Biodiesel can be prepared from various types of vegetable oils or animal fats with the aid of a catalyst. Calcium oxide (CaO) is one of the prospective heterogeneous catalysts for biodiesel synthesis. Modification of CaO by impregnation on silica (SiO2) can improve the performance of CaO as catalyst. Egg shells and rice husks as biomass waste can be used as raw materials for the preparation of the silica modified CaO catalyst. The present study was directed to synthesize and characterize CaO impregnated SiO2 catalyst from biomass waste and apply it as catalyst in biodiesel synthesis. The catalyst was synthesized by wet impregnation method and characterized by x-ray diffraction, x-ray fluorescence, nitrogen adsorption-desorption, and basicity density. The activity of the catalyst in biodiesel synthesis was assayed at different molar ratios of palm oil to methanol ranging from 1:6, 1:9, 1:12 and 1:15. The biodiesel composition was determined by gas chromatography-mass spectroscopy and the properties of the biodiesel were also characterized. The results showed that the CaO impregnated SiO2 catalyst was successfully synthesized based on confirmation by XRD and XRF. The catalyst has a surface area, average pore diameter, total pore volume, and basicity density of 19.38 m2 /g, 3.22 nm, 0.0122 cm3 /g, and 3.4 mmol/g, respectively. The catalyst activity assay indicates that the molar ratio of palm oil to methanol of 1:12 is the optimum condition for biodiesel synthesis. At this molar ratio, 81.4% biodiesel yield was achieved, and it met the quality standards according to ASTM D 6751.